COVID-19 IGG better than PCR for the green pass - Damsa Cristian; Damsa Tomas (Journal of Vaccines and Immunology - Peertechz Publications, 2021)
European Countries and Switzerland provide Green Pass for people who fulfill the two doses' vaccines but also for people who recovered from COVID-19. In order to prove that people recovered they should provide a positive PCR from more than two weeks ago, while IGG positive for COVID-19 is not accepted as a prove of recovery. This policy is not sustained by evidence-based medicine.